Nutritional and phytochemical characterization of radish (Raphanus sativus): A systematic review. (July 2021) - Gamba, Magda; Asllanaj, Eralda; Raguindin, Peter Francis; Glisic, Marija; Franco, Oscar H.; Minder, Beatrice; Bussler, Weston; Metzger, Brandon; Kern, Hua; Muka, Taulant
Abstract: Background: Bioactive compounds in Raphanus sativus (radish) have been used to treat several diseases; therefore, radish has attracted increasing scientific attention due to its nutritional and phytochemical composition. Scope and approach: The available evidence on the nutrient and bioactive composition of radish was systematically assessed. Four databases (PubMed, Embase, Web of Science, and Cochrane trials) were searched, up to September 26th, 2020, for key articles assessing the chemical composition of radish. Two independent reviewers carried out screening, selection of articles, and data extraction. Key findings and conclusions: Of 1214 references, 63 met our inclusion criteria. We found 609 chemical compounds within 23 categories. Red (30% of all studied varieties), white (13%), and black (6%) radish were the most studied varieties. Nutrients and phytochemicals were reported mainly in roots and leaves. The largest categories were flavonoids (38.8% of the reported data), non-flavonoid polyphenols (8.4%), terpenes and derivatives (8.2%), fat and fatty related compounds (6.4%), and glucosinolates and breakdown products (5.6%). Leaves have high concentrations of macronutrients, calcium, potassium, sodium, fiber, fatty acids, and non-flavonoid polyphenols while sprouts are a major source of flavonoids, specifically anthocyanins, β-carotene and vitamin C. Roots are rich in non-flavonoid polyphenols together with terpenes and derivatives, and glucosinolates, the latter also highly concentrated in seeds. Raphanus sativus is a rich source of nutrients and phytochemicals. Leaves and sprouts could be considered part of a healthy diet, and together with roots, they could be explored as raw material for the development of nutraceuticals. Highlights: Raphanus sativus (radish) has high nutritional and phytochemical potential. Flavonoids, especially anthocyanins, are the most studied and reported compounds. Leaves and sprouts have the highest amount of several nutrients and phytochemicals. The identified compounds exert health benefits through various possible mechanisms. Leaves and sprouts could be recommended as part of a healthy diet.